Aplikasi Jasa Sewa Papan Bunga Di Pekanbaru.Florist Menggunakan Metode SUS - Irfan Hibatullah; Susi Erlinda; Torkis Nasution; M. Jamaris (BETRIK, 2025)
The advancement of digital technology offers significant opportunities for micro-enterprises, including flower board rental services in Pekanbaru, which largely rely on conventional ordering methods. This study aims to design and evaluate a prototype Android-based flower board rental application at Pekanbaru.Florist to improve service efficiency and user accessibility. The research employed observation, interviews, and literature studies to identify user needs, followed by system design using React Native and Firebase, and usability evaluation through the System Usability Scale (SUS) involving 30 respondents. The results indicated an average SUS score of 76, categorized as “Good” (grade B), suggesting that the application is user-friendly and well accepted. The prototype effectively addresses major issues such as limited product availability information, slow communication, and ordering errors. In conclusion, the developed application has the potential to enhance operational efficiency and strengthen the competitiveness of local florist businesses. Further development is recommended, particularly by adding interactive features such as live chat and improving the user interface design to optimize user experience